English Teachers’ Perception on The Implementation of Merdeka Kurikulum: A Case Study at Madrasah Tsanawiyah 1 Mataram - Lisda Amalia Wahyuningsih; Lalu Thohir; Lalu Jaswadi Putera; Muhammad Amin (Jurnal Ilmiah Profesi Pendidikan, 2025)
In response to societal changes, the Merdeka Kurikulum has been introduced in Indonesia as a new curriculum that is characterized by flexibility, project-based learning, and the development of students' soft skills, character, literacy, and numeracy. This study aims to know the perceptions of English teachers at MTsN 1 Mataram regarding the implementation of the Merdeka Kurikulum examining its strengths, weaknesses, and the expectations. This research uses a qualitative method and data were collected through interviews and questionnaires. The questionnaire data were analyzed using a Likert scale and categorized by percentage, while the interview data were analyzed using thematic analysis to identify key themes. The results show that English teachers have positive perception towards the Merdeka Kurikulum, as reflected by the 86.25 % agreement level in the questionnaires and supportive responses during interviews. The implementation of the Merdeka Kurikulum at MTsN 1 Mataram is generally perceived positively by English teachers, with its flexibility and student-centered approach being appreciated.